Transformational Adaptation in Agriculture under Climate Change: A Case Study in the Dry Zone of Sri Lanka - Lal Mervin Dharmasiri; Mangala Jayarathne (Indonesian Journal of Geography, 2021)
Transformational adaptation defines as 'changes the fundamental attributes of a system in response to climate and its effects.' Farmers deal with the natural environment and its components such as rainfall, temperature, humidity, and soil condition, which have a high range of variability and uncertainty for their cultivation. The present study focused on the impacts of climate change on the settler community who engage in agriculture as their mainstay and respond to the scenario. Quantitative and qualitative methods have been applied. Twenty samples from a village in the NCP have been selected. Primary outcomes of this study are (a) total awareness of perceptions on climate change; (b) the ambient temperature has been increasing and resulting in more heat stress; (c) frequent and severe occurrence of extreme rainfall anomalies and increasing trend of natural calamities. The area farmers have been adopting several strategies to overcome the negative impacts of climate change, such as transforming from intensification to more intensification that can be identified as Climate Smart Agriculture; crop diversification and adaptation of drought tolerance crops; transforming from agriculture to animal husbandry, and out-migration of unemployed or evicted youth from agriculture to non-agriculture. Institutional involvement is essential to strengthening the adaptative strategies of the people by providing an appropriate crop calendar and suitable crop combination and aware of the way of improving the use of the efficiency of available water for improving the living standard of the people.